ANALYSIS OF FACTORS AFFECTING QUALITY INTERNAL AUDIT RESULTS WITH WORK EXPERIENCE AUDITORS AS MODERATING VARIABLES ON INSPECTORATE OF MEDAN CITY - Ginting, Chrisdayanti (International Journal of Public Budgeting, Accounting and Finance, 2021)
This study aims to analyze the influence of competency measures, independence, moral reasoning, spiritual quotient, and emotional quotient as factors that affect the quality of internal audit results at the Inspectorate of Medan City. This study will also examine the auditor work experience variable which is used as a moderating variable in the research model. The population was all auditors and functional officials of P2UPD who served in the Inspectorate of Medan City who had participated in the training, totaling 48 people. The type of data used is primary data and the data analysis technique used in this study is the Partial Least Square (PLS) approach. The results of this study indicate that the competence and independence of the auditors have a significant positive effect on the quality of internal audit results. Meanwhile, moral reasoning, spirituality; quotient and emotional quotient do not have a significant effect on the quality of internal audit results. The results of this study also indicate that the work experience of the auditors is not able to moderate the influence of competence, independence, moral reasoning, spirituality; quotient and emotional quotient on the quality of internal audit results.